The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1073/pnas.0805054105
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants targeting innate and adaptive immunity synergize to enhance tumor immunotherapy

Abstract: Because of mechanisms of self-tolerance, many tumor-specific CD8 T cells exhibit low avidity for tumor antigens and would benefit from strategies that enhance their numbers and effector function. Here we demonstrate that the combined use of two different types of immune adjuvants, one that directly targets the CD8 cell, IL-2/anti-IL-2 mAb complexes, and one that targets the innate immune system, poly(I:C), can achieve this goal. Provision of IL-2/mAb complexes was found to enhance the activation and effector f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 46 publications
3
45
2
Order By: Relevance
“…Kamimura et al 26 showed that coinjection of S4B6 mAb with a plasmid carrying murine il2 cDNA is capable to reduce the number of B16 melanoma lung metastasis to half that seen with injection of the plasmid alone. Other studies have described the antitumor activity of IL-2 immunocomplexes, which was especially prominent when coadministrated with poly I:C. 33 However, the tumor elimination described in our work was achieved by adoptive transfer of tumor-specific T cells followed by treatment with IL-2 immunocomplexes and was thus a rather artificial model of tumor treatment. The potential of IL-2 immunocomplexes for rapid generation of a functional NK cell compartment after bone marrow transplantation was highlighted by Prlic et al, 34 and the implications for preventing the tumor relapse was discussed.…”
Section: Discussionmentioning
confidence: 51%
“…Kamimura et al 26 showed that coinjection of S4B6 mAb with a plasmid carrying murine il2 cDNA is capable to reduce the number of B16 melanoma lung metastasis to half that seen with injection of the plasmid alone. Other studies have described the antitumor activity of IL-2 immunocomplexes, which was especially prominent when coadministrated with poly I:C. 33 However, the tumor elimination described in our work was achieved by adoptive transfer of tumor-specific T cells followed by treatment with IL-2 immunocomplexes and was thus a rather artificial model of tumor treatment. The potential of IL-2 immunocomplexes for rapid generation of a functional NK cell compartment after bone marrow transplantation was highlighted by Prlic et al, 34 and the implications for preventing the tumor relapse was discussed.…”
Section: Discussionmentioning
confidence: 51%
“…Given these properties, IL-2/S4B6 complexes could be used therapeutically in metastatic malignancies and chronic viral infection. In support of this notion, several groups have reported favorable results using IL-2/S4B6 complexes either as a monotherapy or in combination with another agent (such as Toll-like receptor ligand, agonist anti-OX40 mAb, or peptide vaccine) in various cancer models, including B16 melanoma, Lewis lung carcinoma, MC38 colon carcinoma, MCA-205 sarcoma, and TRAMP-C1 prostate carcinoma [31,[48][49][50][51][52][53]. Moreover, IL-2/S4B6 complexes have shown efficacy in models of acute and chronic infection [54,55].…”
Section: Il-2/mab Complexesmentioning
confidence: 93%
“…In contrast, JES6-1 anti-mIL-2 mAb produced IL-2/mAb complexes that interacted almost exclusively with immune cells expressing high levels of CD25 along with βγ IL-2R; these CD25-directed complexes, designated IL-2/mAb CD25 complexes, induced selective expansion of CD25 + CD4 + Tregs (8). In addition to IL-2, cytokine/mAb complexes can also be generated using IL-3, IL-4, IL-6, or IL-7, which have been successfully used in various animal models, including viral infections, antitumor responses, autoimmune disease, and graft tolerance (8,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Il-2 Is Crucial To T Cell Homeostasis Especially Of Cd4mentioning
confidence: 99%